Pengaruh Likuiditas dan Profitabilitas terhadap Return Saham pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Aminar Sutra Dewi; Ijratul Fajri (JURNAL PUNDI, 2019)
To invest in the capital market, investors must know that in addition to receiving profits, they will also suffer losses. One of the motives of inventors to invest is to get a maximum rate of return with certain risk or obtain a certain rate of return on minimal risk. This study aims to examine the effect of liquidity and profitability on stock returns. The population is a manufacturing company which are listed in Indonesia Stock Exchange in 2013-2017 periods. The sampling technique uses a purposive sampling method with predetermined criteria and obtained a sample of 34 companies with 170 observations. The data of the financial statement of the companies has been obtained from the official website of IDX. The analytical method used is regression analysis of panel data with the help of application E-Views 8. Panel data regression can be estimated using three models, namely Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). To get the best model, a further test was used, namely the Chow Test and Hausman Test. From the results of the estimation model, it is found that REM is the best model in this study. Furthermore, the results of the study show that liquidity has a positive and not significant effect on stock returns, while profitability has a positive and significant effect on stock returns.